A compact microstrip antenna for ultra wideband applications - Kasi B.; Ping L.C.; Chakrabarty C.K. (2023)
In this study, a simple and compact ultra-wideband (UWB) patch antenna with rectangular slot is presented. The fabricated antenna consists of a rectangular patch tapered from a microstrip feeding structure and a truncated ground plane. The proposed antenna is etched onto a FR4 printed circuit board (PCB) with an overall size of 28 mm 29 mm 1.6 mm. Simulated and experimental results are compared and are shown to be in good agreement. Experimental results indicate that the antenna achieved an UWB impedance bandwidth (S11 < -10 dB) ranges from 3.8 to 12 GHz. The small antenna exhibits a good voltage standing wave ratio (VSWR) performance and its E- and H-plane radiation patterns are stable over the UWB frequency range. The simulated result shows that the designed antenna can achieve a gain between 1.5 and 4.5 dBi against frequency. Besides, the group delay is less than 0.4 ns over the operating frequency band. These characteristics make the designed antenna suitable for various UWB applications. EuroJournals Publishing, Inc. 2011.